NDN blockchain network topology performance analysis and optimization model - XIU Jiapeng; LIU Huixin; YANG Zhengqiu; ZHANG Dehao; GUO Shaoyong (Tongxin xuebao)
In order to further improve the network layer transmission performance of the blockchain system based on named data networking (NDN), a performance analysis and optimization model for the NDN blockchain network topology was proposed. The model included methods for calculating block synchronization time and block transmission redundancy in the NDN blockchain system, a network topology scoring system based on block synchronization time and block transmission redundancy, and an optimization scheme based on network topology attributes and scores. The model addressed the incompatibility of blockchain network topology evaluation models based on TCP/IP with NDN blockchain. Given the known network environment parameters and NDN network layer data synchronization methods, the performance metrics were calculated and analyzed, providing optimization solutions for actual NDN blockchain networking. The experimental results show that after analyzing and optimizing a 9-node network topology using this model, the optimized network topology reduces block synchronization time from 2.95 seconds to 2.37 seconds, a decrease of 19.66%, while maintaining the block transmission redundancy unchanged, and increases the score from 0.64 to 0.82. This demonstrates that the model has a good effect on improving the performance of NDN blockchain.